Integrative GC-MS, network pharmacology, and molecular dynamics elucidate synergistic anti-diabetic mechanisms of Chongqing Citrus reticulata ‘Dahongpao’ volatile oil via multi-target stabilization - Wanting Zhong; YaYi Xiong; Jie Luo; Shujaat Ahmad; Jian Wang (PLoS ONE, 2026)
Background Diabetes mellitus involves complex pathogenesis requiring multi-target interventions. Citrus reticulata ‘Dahongpao’ from Chongqing exhibits anti-diabetic potential, but its mechanisms remain elusive. Methods We employed an integrative strategy: GC-MS identified 82 compounds (96.61% coverage), dominated by D -limonene (62.48%). Network pharmacology revealed 36 diabetes-related targets. Molecular docking prioritized ligands (thymol: −6.8 kcal/mol with FABP1; n-hexadecanoic acid: −6.7 kcal/mol with PTGS2). Critical validation was achieved via 100-ns molecular dynamics (MD) simulations and MM-GBSA binding free energy calculations. Results MD simulations demonstrated structural stability (RMSD < 2.5 Å) for core complexes (e.g., CYP19A1/thymol). MM-GBSA quantified robust binding for FABP1/dodecanoic acid (−43.26 kcal/mol) and PTGS2/n-hexadecanoic acid (−43.93 kcal/mol), driven by van der Waals forces. Hydrogen bond dynamics revealed persistent interactions (e.g., thymol–THR102 in FABP1), while RMSF highlighted ligand-induced flexibility in fatty acids. Pathway analysis implicated PPAR signaling and insulin resistance. Conclusion Citrus reticulata ‘Dahongpao’ essential oil combats diabetes through synergistic multi-target modulation, validated by dynamic ligand–protein stability and energetics. This study presents an in silico framework that integrates phytochemical profiling and computational analyses to facilitate natural product drug discovery.